Succeeding at the interview[videorecording] : hints from the real world - Harding, Ben; Martin, Julia (Video Education Australasia, 2002)
This video looks at a critical element in the job seeking process, the job interview, and outlines what interviewees should do to prepare themselves, how they can acquit themselves well during the interview, what the employer wants to find out, and how to follow up and learn from mistakes after the event. DVD.